DESIGN FOR INCLUSIVE COMMUNITIES: UNIVERSITIES AS DRIVERS OF SUSTAINABLE AND SOCIAL ENGAGEMENT NETWORKS IN LOCAL COMMUNITIES - Cardoso, Ana Sofia Carneiro e (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Communities and networks constitute complex socio-cultural ecosystems wherein participatory design and art practices assume a central role in fostering collaborative creativity and addressing collective challenges. The infusion of participatory design into these networks serves as a catalyst for social innovation, facilitating the active engagement of community members in co-creating their shared environments. Social design emerges as a strong tool, transcending disciplinary boundaries to harness the capacities of art and design in responding to intricate societal issues. This interplay between participatory design and art practices becomes a dynamic mechanism instigating positive transformations within communities, fostering diverse perspectives and inclusive solutions. University-level students can play a crucial role in the convergence of art and design activism, enhancing the impact of interventions with a socio-political dimension. As active participants in civic engagement through art and design, these students become vital advocates for social justice, contributing substantively to community empowerment and proactive determination of future trajectories. The genesis of the "O Bairro está IN(clusivo)" [The Neighborhood is IN(clusive)] project exemplifies this synergy. Promoted by ESAD — College of Art and Design and rooted in the principles of dream, imagination, fabulation, and self-build, the project endeavors to contribute to societal betterment through design and architecture, emphasizing positive transformation of Cruz de Pau's (social housing community in Matosinhos, Portugal) urban space through active community participation. Financed under the “Healthy Neighborhoods Program”, a governmental initiative to enhance the quality of life in vulnerable territories, the project focuses on Cruz de Pau—a neighborhood with diverse demographic profiles and varying economic and social needs. The project engages in workshops and participatory activities involving three generations —seniors, young people, and adolescents —, aiming to improve the surrounding space and leverage local knowledge. Through art and creativity, the project activates social and urban "regeneration," fostering participation and identification between inhabitants and their surroundings, while showcasing the effective transformative power of a united community